Centre of mass intracyclic velocity variation in three variants of the front crawl water polo technique - Pereira, F.; Figueiredo, P.; Goncalves, P.; Vilas-Boas, J. P.; Fernandes, R. J.; Machado, L. (ISBS - Conference Proceedings Archive (Konstanz), 2011)
The purpose of this study was to analyse the intracyclic velocity variation (IVV) of the centre of mass (CM) in the x, y, z axes during the stroke cycle event in front crawl, water polo front crawl and water polo front crawl while leading the ball. Ten national level water polo players performed 3x15 m at maximum intensity in each variant of the front crawl technique, being videotaped by six cameras (two above and four underwater). One complete stroke cycle was analyzed for each 15 m test using the APASystem. The numerical treatment was conducted using MATLAB software. IVVx and IVVz showed less variation in the water polo front crawl, and IVVy showed less variation for the water polo front crawl leading the ball. These suggest that water polo players have a greater proficiency in water polo specific swimming techniques rather than in front crawl.